The sustainable Development of mountain regions: A paradigm shift and new considerations - Li Pun, H.H.; Mares, V. (International Centre for Integrated Mountain Development, 2000)
This paper describes the reasons for the urgent need to dedicate substantial research and Development efforts to mountain areas, and discusses some of the collaborative research in which ILRI is currently playing a major role. The paper focusses on the sustainable Development of mountain ecoystems, key issues, and challenges; some research and Development experiences, with particular reference to the collaboration between ILRI and International Centre for Integrated Mountain Development, CIP, farmers associations and NGOs; and identification of some appropriate issues for R & D in sustainable mountain Development.